Social support for parents of children with leukemia - Carolin, Putri; Fetriyah, Umi Hanik; Palimbo, Adriana; Mahmudah, Rifa'atul (Ananda - Health & Education Foundation, 2025)
Background: The prevalence of children with leukemia tends to increase. Leukemia treatment requires a long period of time which has physical, psychological and social impacts on children and parents which affect their quality of life. Social support obtained protects parents in facing times of stress. Objective: To determine social support for parents who have children with leukemia. Method: Quantitative research type. The research sample consisted of 30 respondents taken using convenient sampling techniques. Data collection instrument using a questionnaire. Data were analysed with descriptive statistics. Results: The majority of parents who have children with leukemia are over 35 years old (73.3%), have elementary education (43.3%), work as housewives (53.3%), and most parental category is mothers (80.0%). Mean value of social support (66.43), highest social support category (76.7%). Social support questionnaire items are highest in the family dimension of form of emotional support and lowest form of emotional support. Friend dimension is lowest form of instrumental support and highest form of emotional support. The dimension of closest person is the highest form of emotional support and lowest is the form of instrumental support. Conclusion: Social support from family, friends, and close people is needed for parents who have children with leukemia. Because it can provide positive energy for parents and children, the attention, security, and comfort provided can increase their confidence. Recommendations for friends and parents to provide instrumental support in form of being ready to help parents who have children with leukemia when experiencing difficulties both facilities and material.